Efficacy of exclusive human milk diet in preterm infants weighing ≤1500 g: a single-center COHORT study - Pulokkodan, Ismail; Hariram, Maralakunte R.; Anup, Pushpanjali; Duraiswamy, Venkatesh S. (International Journal of Contemporary Pediatrics, 2024)
Background: Preterm infants have high nutrition needs for growth and survival as they are at high risk of mortality and morbidity. An exclusive human milk diet (EHMD) that comprises human milk (HM) either expressed breast milk (EBM) or pasteurized donor human milk (PDHM), fortified with a 100% human milk-based fortifier (HMBF) could provide with safe nutritional strategy in preterm infants. Methods: This single-center, prospective cohort study included a cohort of 25 preterm infants ≤34 weeks of gestation weighing ≤1500 g at birth who were fed with EHMD when the feed volume reached 100 ml/kg/day until the infant was fit for discharge. Results: Of the 25 infants enrolled in the study the mean gestational age was 29.6±1.6 weeks and birth weight was 1171±230.7 g. The mean weight gain was 25.5±5.5 g/day and the mean growth velocity was 17.8±3.4 g/kg/day. Feeding intolerance was observed in 4 infants (16%), the average days to reach full feeds was 12.4±4.9 days and there was no necrotizing enterocolitis (NEC) observed. Conclusions: EHMD was well tolerated by the infants with better weight gain. These findings demonstrate that EHMD is a safe and effective nutritional strategy in the management of preterm infants. However, a large RCT (randomized clinical trial) is required to evaluate the efficacy of EHMD.